Konsep Wanita Karier Era 4.0 Persepktif Al-Qur’an - Silvia Rahma Yanti; Nasrulloh (Jurnal test, 2024)
This research aims to analyze the concept of career women in the era of the Industrial Revolution 4.0 from the perspective of the Koran. This research uses library research with a normative qualitative approach that focuses on analyzing available library data and articles. The results of the research show that the concept of career women from the Al-Qur’an perspective is that there is no prohibition for women from having a career in their lives, women have the right to work and have a career just like men, especially in the 4.0 era which is very sophisticated with today’s rapid technological advances. . In accordance with Q.S. An-Nisa’ verse 32 explains that men get a share of what they work for, as well as women get a share of what they work for, this is in accordance with how much effort and ability they have. So a career woman must comply with the requirements as a career woman in the world of work, including maintaining a balance between family and career and being able to maintain her honor as a Muslim woman. So they avoid slander and other negative impacts that will bring harm to themselves, their families and society.